The Ethnicity Distraction? Political Credibility and Partisan Preferences in Africa - Keefer, Philip (2012)
Much of the research on ethnicity, development and conflict implicitly assumes that ethnic groups act collectively in pursuit of their interests. Collective political action is typically facilitated by political parties able to make credible commitments to pursue group interests. Other work, however, emphasizes the lack of political credibility as a source of adverse development outcomes. Evidence presented here uses partisan preferences across 16 Sub-Saharan African countries to distinguish these positions. The evidence is inconsistent with the credibility of party commitments to pursue collective ethnic interests: ethnic clustering of political support is less widespread than expected; members of clustered ethnic groups exhibit high rates of partisan disinterest and are only slightly more likely to express a partisan preference; and partisan preferences are more affected by factors, such as gift-giving, often associated with low political credibility. These findings emphasize the importance of looking beyond ethnicity in analyses of economic development.